Interfacing reprogrammable universal remote controller with multimedia PC - E., C.Tan; Abdul Rahman, Abdul Wahab; H., W. Yong (Elsevier, USA, 1998)
The paper describes the design and implementation of a low-cost electronic circuit which can be incorporated into a universal remote controller that is used to control electronic appliances such as televisions, video cassette recorders and audio systems. In an educational or a conference environment, the circuit can be used to facilitate computer-assisted presentations by acting as an interface between the universal remote controller and a personal computer (PC) so that multimedia database applications can be developed on a PC to retrieve desired video clips on a video cassette tape and play them on a TV via the universal remote controller.